Literature Review : PENGARUH PLYOMETRIC TRAINING TERHADAP JUMPING PERFORMANCE PADA ATLET - Tika Dwi Damayanti (2021)
Background: Athletes are one of the professions in the field of sports that require components to support their performance, these components include sprinting, agility, jumping, power and others. To improve this performance, plyometric training can be used. Objective: Jumping Performance is an essential component in supporting athlete performance. This literature study aims to examine literature, journals, articles, or research results with the topic of the influence of plyometric training on jumping performance in athletes. Methods: Search for sources of literature, journals, articles, research results in several databases such as Google Scholar, Science Direct, Elsevier, PubMed and Litmaps using certain keywords in the 2015-2020 period. From the results of the literature search, 7 articles were found and only 5 articles met the source inclusion criteria. The methodological quality assessment of 5 articles was assessed with the Scimago Journal & Country Rank (SJR). Analysis of the 5 journals was carried out based on the suitability of the topic, research methods used, samples, interventions, instruments/parameters, and the results of each article. Result: The results of a literature review of 5 articles have shown thatplyometric training can improve jumping performance in athletes. Conclusion: Plyometric training can improve jumping performance in athletes. Keywords : Plyometric training, jumping, jumping performance, athlete